Histologic Effects of Resurfacing Lasers - Freedman, Joshua R.; Greene, Ryan M.; Green, Jeremy B. (Facial Plastic Surgery, 2014)
By utilizing resurfacing lasers, physicians can significantly improve the appearance of sun-damaged skin, scars, and more. The carbon dioxide and erbium:yttrium-aluminum-garnet lasers were the first ablative resurfacing lasers to offer impressive results although these earlier treatments were associated with significant downtime. Later, nonablative resurfacing lasers such as the neodymium:yttrium-aluminum-garnet laser proved effective, after a series of treatments with less downtime, but with more modest results. The theory of fractional photothermolysis has revolutionized resurfacing laser technology by increasing the safety profile of the devices while delivering clinical efficacy. A review of the histologic and molecular consequences of the resurfacing laser–tissue interaction allows for a better understanding of the devices and their clinical effects.
Keywords: resurfacing; laser; histology; ablative; nonablative